TYPES OF ELECTORAL TECHNOLOGY USED IN ELECTION CAMPAIGNS AND THEIR SPECIFIC FEATURES - Boltabaev Bakhtiyor Sabirjonovich (Sciental Journals Publishing, 2025)
This article provides feedback on the effective use of new technologies in election processes, useful quotes of political advertising, campaign and propaganda masks, which are considered an integral part of election campaigns.